ANALISIS STILISTIKA NOVEL DARI HARI KE HARI KARYA MAHBUB DJUNAIDI DAN RELEVANSINYA SEBAGAI MATERI AJAR BAHASA INDONESIA DI SEKOLAH MENENGAH ATAS - Cahyono, Nur; Andayani, Andayani; Mujiyanto, Yant (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2018)
The aims of this research are to describe diction (word choise, figure of a speech, imagery of Dari Hari Ke Hari’s novel by Mahbub Djunaidi, and the relevance of the results of studies as Bahasa Indonesia teaching material for the Senior High School. This study is a qualitative descriptive with content analysis method. The result showed that. First, the use of diction (choice words) includes concrete words, connotative words, word greetings or self-names, vulgar words, words of absorption, regional vocabulary, and words with natural reality. Second, the use of language style (Figure of a speech) includes simile, metaphor, personification, depersonification, allegory, antithesis, pleonasme, periprasis, anticipation, epanortosis, satire, paradox, climax, anti-climax, allusion, atonomation, eroteris, asyndeton, polisedenton, epizeukis, anaphora, and epystrofa. Third, the use of imagery includes visual imagery, motion imagery, olfactory imagery, tactical imagery, and auditory images. Fourth, Dari Hari Ke Hari’s novel can be used as a teaching material in high school literature class XII curriculum of 2013, ie at base competence understand the structure and rules of novel text.